Progress in Developing Improved Citrus Rootstocks to Mitigate HLB - Grosser, Jude; Gmitter, Fred; Dutt, Manjul (EDIS, 2022)
Exploiting citrus genetic diversity is the key for defeating HLB. Plant species have survived for millennia with evolving, hostile pathogens – HOW? Through natural selection within genetically diverse populations, tolerant or resistant individuals survive and intermate, get through the bottleneck, and the species evolves. Current citriculture is based on extremely limited genetic diversity, approaching monoculture, and this has contributed to the current HLB crisis. Facilitated by biotechnology, Citrus breeders are exploiting the broad and unique genetic diversity from elite parents, followed by robust screening. As citriculture utilizes rootstocks, it is possible that a resistant or highly tolerant rootstock could mitigate the disease in any commercial scion. This would be the ultimate solution to HLB!